Manajemen Santri: Peningkatan Prestasi dan Layanan Santri Dayah Mataqu Ustman Bin Affan Lhokseumawe - Salma, Salma; Syafri, Muhammad (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study aims to describe the mechanisms of student admission, the development of active students, and the services provided to students at Dayah MATAQU Ustman Bin Affan. The research employs a descriptive qualitative approach, focusing on students (ṭalabah) as the primary subjects. The main data sources include the head of the madrasa, teachers, and the head of student care. Data collection techniques encompass in-depth interviews, observation, and document studies. Data analysis is conducted through three stages: data reduction, data display, and data verification. The results of the study reveal that Dayah MATAQU employs various strategies for student admissions, including promotion to nearby schools, the use of social media, online registration, and the establishment of registration points in key student areas. The admission process involves academic tests, interviews, and evaluations of report card grades and School Final Exams. Accepted students must meet criteria that include academic performance, behavior, and health. Student development includes routine worship activities, extracurricular activities, and disciplinary actions according to violations. Services provided to students cover administration, learning processes, rule enforcement, communication with families, and guidance by ustadz and ustadzah. These comprehensive services have led to student achievements at national and local levels and increased self-confidence through the Tasmī’ Akbar activities. The study recommends that Dayah MATAQU continue to enhance training programs for ustaz and ustazah to improve the quality of services and student development. It is also essential to expand extracurricular programs that support the development of students' character and achievements.